Development of articulate storyline-based learning media to facilitate student self-regulated learning in similarity and congruence - Maruli, Fitryani; Saragih, Sehatta; Suanto, Elfis (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study emphasizes the importance of fostering self-regulated learning among students. The aim is to develop Articulate Storyline-based learning media on the topic of congruence that is both valid and practical for junior high school students. The development process follows the 4D framework: Define, Design, Develop, and Disseminate. The participants of this research were ninth-grade students at SMP Negeri 35 Pekanbaru. Data for this study were collected through literature reviews, design validation, and questionnaires using instruments such as validation questionnaires, self-regulated learning questionnaires, and student response questionnaires. The validity analysis results indicate that the learning media is highly valid, with an average score of 3.75. The practicality analysis from the large-group test shows that the media is highly practical, with an average score of 0.90. Additionally, the self-regulated learning score is 78.18%, categorized as good. Based on these results, the learning media is suitable for use, having fulfilled both validity and practicality requirements.